1989
DOI: 10.1016/0014-5793(89)80661-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquinones in the regulation of lipid metabolism in rat thymocytes

Abstract: The effect of ubiquinones Q-l, Q-2, Q-8 and Q-9 on lipid metabolism in rat thymocytes in vitro was studied. The cells were incubated in a medium containing ubiquinones within the concentration range from 1 to 100 #M. A 2-fold decreased cholesterol synthesis was observed in thymocytes incubated with ubiquinone Q-9 at a concentration of exogenous ubiquinone of no less than 40 #M. Incubation of thymocytes with ubiquinones UQ-I and UQ-2 that are characteristic of rats (40 #M and I00/tM) resulted in a decrease of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A significant decrease in cholesterol synthesis and a subsequent drop in the cholesterol concentration of the cellular membranes were observed in rats fed a diet supplemented with ubiquinone Q 9 . Additionally, the inhibition of cholesterol synthesis in lymphocytes cultivated in vitro with coenzyme Q 9 was demonstrated [29, 30]. Interestingly, our data indicated that the preintervention with dietary antioxidants decreased the magnitude of the inflammatory response, but diet did not amplify the effect of IKK Inhibitor XII.…”
Section: Discussionmentioning
confidence: 72%
“…A significant decrease in cholesterol synthesis and a subsequent drop in the cholesterol concentration of the cellular membranes were observed in rats fed a diet supplemented with ubiquinone Q 9 . Additionally, the inhibition of cholesterol synthesis in lymphocytes cultivated in vitro with coenzyme Q 9 was demonstrated [29, 30]. Interestingly, our data indicated that the preintervention with dietary antioxidants decreased the magnitude of the inflammatory response, but diet did not amplify the effect of IKK Inhibitor XII.…”
Section: Discussionmentioning
confidence: 72%